ANALISIS KEBUTUHAN NSTRUMEN UJIAN KENAIKAN TINGKAT PADA PERGURUAN KEI SHIN KAN - Irpan Wahyudi Nasution; Rommy Manaluksuk Saputra Napitupulu; Syahputra Manik (STKIP Subang, 2026)
This study aims to analyze the need for a promotion examination assessment instrument at Perguruan Kei Shin Kan. This research uses a quantitative approach with a descriptive research design. The research subjects consisted of coaches/examiners and athletes involved in the promotion examination process. Data were collected using a questionnaire with a Likert scale. The data were analyzed using descriptive percentage techniques. The results showed that 78.6% of respondents strongly agreed and 14.3% agreed on the need for a systematic assessment instrument. This indicates that the need for a promotion examination assessment instrument is in the very high category. Therefore, an objective, systematic, and standardized assessment instrument is required to improve the quality of evaluation in the promotion examination process.